"Precisa ter gente!" Uma análise do MST e das crianças Sem Terrinha - Rudi, Luciana de Matos (2024)
This doctoral thesis aims to present the conception of childhood and children within the Movimento dos Trabalhadores Rurais Sem Terra – MST, based on the formulations made by the Movement itself, as well as the reflections of the "Sem Terrinha" children. The manner in which they engage with this conception, as well as the physical, symbolic, and political space they occupy within the organization, are elements discussed in this study. To achieve this, two “Encontros das Crianças Sem Terrinha" (Gatherings of the Sem Terrinha" children) were ethnographically studied, and educational documents and programs created by and for them were analyzed. This includes live broadcasts and programs, especially during the [voluntary] isolation periods of the pandemic, where ethnography was predominantly virtual. Furthermore, the thesis establishes a connection between the actions of the children and the broader initiatives undertaken by the MST in the struggle for land through popular agrarian reform, political agenda setting, and proposals to postpone the end of the world by creating a new world, with agroecology as a foundational national project. In this sense, the "Sem Terrinha" children emerge as significant agents of change, actively participating alongside the Landless Workers on various fronts.